2014
DOI: 10.5624/isd.2014.44.4.287
|View full text |Cite
|
Sign up to set email alerts
|

Cone-beam computed tomography findings of impacted upper canines

Abstract: PurposeTo describe the features of impacted upper canines and their relationship with adjacent structures through three-dimensional cone-beam computed tomography (CBCT) images.Materials and MethodsUsing the CBCT scans of 79 upper impacted canines, we evaluated the following parameters: gender, unilateral/bilateral occurrence, location, presence and degree of root resorption of adjacent teeth (mild, moderate, or severe), root dilaceration, dental follicle width, and presence of other associated local conditions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 31 publications
2
19
0
3
Order By: Relevance
“…When we consider gender, we observe that there is a striking higher frequency female patients within our population. This is in line with the findings in the current literature (da Silva Santos et al, 2014).…”
Section: Association Between Teeth Position and Treatmentssupporting
confidence: 94%
See 1 more Smart Citation
“…When we consider gender, we observe that there is a striking higher frequency female patients within our population. This is in line with the findings in the current literature (da Silva Santos et al, 2014).…”
Section: Association Between Teeth Position and Treatmentssupporting
confidence: 94%
“…The maxillary impacted canine is more often located palatally (85%) than labially (15%) (Bishara, ; Cooke & Wang, ; Ericson & Kurol, ; Ferguson, ; Grover & Lorton, ; Warford, Grandhi, & Tira, ). Root dilaceration is reported to be present in up to 59.5% of the cases (da Silva Santos et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, cone-beam computed tomography (CBCT) has become an alternative to conventional CT in diagnosis and treatment planning of impacted teeth [ 5 , 6 ]. Also, CBCT has many advantages, it is reliable, reduces distortion, costs less, and allows a diminished radiation dose [ 7 ]. Bjerklin and Ericson found that, after 3D assessment of maxillary impacted canines, orthodontic treatment plans were changed in nearly half of the cases [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Gömülü maksiller kanin dişlerin, lateral dişlerde daha sık rezorpsiyona sebep olduğu yapılan çalışmalarda bildirilmiştir (8,13). Literatürdeki bazı çalışmalarda (9,24,25) komşu dişlerde görülen rezorpsiyon oranı %27 ile % 35 arasında değişirken çalışmamızda rezorpsiyon oranı %18 olarak bulundu. Bu oran çalışmadan çalışmaya değerlendirilen gömülü diş sayısının ve kullanılan görüntüleme yöntemlerinin farklı olması nedeniyle farklılık gösterebilir.…”
Section: Gereç Ve Yöntemunclassified